Performance of Japanese patients in registrational studies. (23rd November 2021) - Goto, Yasushi; Arakawa, Sayaka; Shirasawa, Masayuki; Higashiyama, Ryoko; Baba, Keisuke; Masuda, Ken; Shinno, Yuki; Matsumoto, Yuji; Okuma, Yusuke; Yoshida, Tatsuya; Horinouchi, Hidehito; Yamamoto, Noboru; et al.
Abstract: Introduction: The accelerated development of lung cancer treatments has resulted in a single global study that is sufficient for a new agent and indication to be approved. Not all new treatments predominate globally, and differences in standards of care may influence the efficacy of treatments in the real world. Methods: The results from Japanese domestic trials and global trials that included a subset population of Japanese patients were evaluated for 18 genomic targeted agents and immune therapies approved after 2000. The results were collected from drug applications that were reviewed for treatment approval in Japan. Results: Japan is one of the first countries to approve and fully reimburse new agents around the world. Alectinib and nivolumab, which were first developed by Japanese pharmaceutical companies, were evaluated in an independent domestic trial, which resulted in their early approval. For most other indications, 1.1–15.8% of the patients who participated in pivotal registration studies were Japanese, and their treatment results were comparable to those of the overall population. Overall survival was less likely to be improved by four agents for which the post-protocol therapy might have been different in Japan than in other countries. Conclusions: Overall, a positive result in a global trial was emulated in Japanese patients and led to the approval of a new standard treatment in Japan. Early approvals were attained by either participating in the global registrational study or conducting a domestic phase II study. The higher efficacy of new agents may be an issue in the future, as Japanese patients had early access to the new agent and may receive better treatment after the trial. Abstract : Japanese and global registrational studies were evaluated. The performance of Japanese patients on the new treatment was equivalent to other patient groups.